Synthesis conditions of ZBLAN glass for mid-infrared optical components - Cimek, Jarosław; Forestier, Xavier; Stepien, Ryszard; Klimczak, Mariusz; Buczynski, Ryszard (Photonics Letters of Poland, 2018)
We report on successful synthesis of ZBLAN glass. Different purity of zirconium tetrafluoride used for synthesis and fluorinating agents were analyzed to obtain high optical quality glass. Among fluorinating agents we used ammonium bifluoride, xenon difluoride and sulfur hexafluoride. The best results in form of synthetized glasses have transmission window extending from 0.2 to 8.0 um, which allows to fabricate fibers for mid-infrared applications. Full Text: PDF References R. Stępień, J. Cimek, D. Pysz, I. Kujawa, M. Klimczak, and R. Buczyński, Soft glasses for photonic crystal fibers and microstructured optical components, Opt. Eng. 53, 071815 (2014). CrossRef D. Pysz, I. Kujawa, R. Stępień, M. Klimczak, A. Filipkowski, M. Franczyk, L. Kociszewski, J. Buźniak, K. Haraśny, R. Buczyński, Stack and draw fabrication of soft glass microstructured fiber optics, Bull. Pol. Acad. Sci.-Tech. Sci., 62(4), 667-683 (2014). CrossRef R. Kasztelanic, I. Kujawa, R. Stępień, K. Haraśny, D. Pysz and R. Buczyński, Molding of soft glass refraction mini lens with hot embossing process for broadband infrared transmission systems, Infrared Phys. Technol. 61, 299-305 (2013). CrossRef Moynihan C.T. (1987) Crystallization Behavior of Fluorozirconate Glasses. In: Almeida R.M. (eds) Halide Glasses for Infrared Fiberoptics. NATO ASI Series (Series E: Applied Sciences), 123, Springer, Dordrecht. CrossRef M. R. Majewski, R. I. Woodward, S. D. Jackson, Dysprosium-doped ZBLAN fiber laser tunable from 2.8?m to 3.4?m, pumped at 1.7?m, Opt. Lett. 43, 971-974 (2018). CrossRef G Bharathan, R. I. Woodward, M. Ams, D. D. Hudson, S. D. Jackson, A. Fuerbach, Direct inscription of Bragg gratings into coated fluoride fibers for widely tunable and robust mid-infrared lasers, Opt. Express 25, 30013-30019 (2017). CrossRef Y. Shen, Y. Wang, H. Chen, K. Luan, M. Tao, J. Si, Wavelength-tunable passively mode-locked mid-infrared Er3+-doped ZBLAN fiber laser, Sci. Rep. 7, 14913 (2017). CrossRef J. Méndez-Ramos, P. Acosta-Mora, J. C. Ruiz-Morales, T. Hernández, M. E. Borges, P. Esparza, Heavy rare-earth-doped ZBLAN glasses for UV?blue up-conversion and white light generation, J. Lumin. 143, 479-483 (2013). CrossRef X. Jiang, N. Y. Joly, M. A. Finger, F. Babic, G. K. L. Wong, J. C. Travers, P. St. J. Russell, Deep-ultraviolet to mid-infrared supercontinuum generated in solid-core ZBLAN photonic crystal fibre, Nat. Photonics 9, 133?139 (2015). CrossRef X. Jiang, N. Y. Joly, M. A. Finger, F. Babic, M. Pang, R. Sopalla, M. H. Frosz, S. Poulain, M. Poulain, V. Cardin, J. C. Travers, P. St. J. Russell, Supercontinuum generation in ZBLAN glass photonic crystal fiber with six nanobore cores, Opt. Lett. 41, 4245-4248 (2016). CrossRef A. Medjouri, E. B. Meraghni, H. Hathroubi, D. Abed, L. M. Simohamed, O. Ziane, Design of ZBLAN photonic crystal fiber with nearly zero ultra-flattened chromatic dispersion for supercontinuum generation, Optik 135, 417?425 (2017). CrossRef D. C. Tee, N. Tamchek, C. H. Raymond Ooi, Numerical Modeling of the Fundamental Characteristics of ZBLAN Photonic Crystal Fiber for Communication in 2?3 ?m Midinfrared Region, IEEE Photon. J. 8, 4500713 (2016) . CrossRef Y. Dai, K. Takahashi, I. Yamaguchi, Thermal oxidation of fluorozirconate glass and fibres, J. Mater. Sci. Lett. 12, 1648?1651 (1993). CrossRef P. Hlubina, White-light spectral interferometry with the uncompensated Michelson interferometer and the group refractive index dispersion in fused silica, Opt. Commun. 193, 1-7 (2001). CrossRef F. Gan, Optical properties of fluoride glasses: a review, J. Non Cryst. Sol. 184, 9-20 (1995). CrossRef A. Filipkowski, B. Piechal, D. Pysz, R. Stepien, A. Waddie, M. R. Taghizadeh, and R. Buczynski, Nanostructured gradient index micro axicons made by a modified stack and draw method, Opt. Lett. 40, 5200-5203 (2015). CrossRef R. Kasztelanic, A. Filipkowski, D. Pysz, R. Stepień, A. J. Waddie, M. R. Taghizadeh, and R. Buczynski, High resolution Shack-Hartmann sensor based on array of nanostructured GRIN lenses, Opt. Express 25, 1680-1691 (2017). CrossRef